Effects of cystic fibrosis sera on Proteus vulgaris motility - Cohen, F. L. (1974)
Suspensions of Proteus vulgaris were rapidly agglutinated by serum from cystic fibrosis patients. Serum from obligate heterozygotes exhibited a mean agglutination time that was significantly less than that observed for 128 controls. The agglutinating property was observed to be transmitted through several generations and through both maternal and paternal branches of the pedigrees. Qualitative differences were noted, with CF sera inducing the formation of clumps that were two- to 10-fold larger than those observed in heterozygotes. The serum factor responsible for P. vulgaris agglutination was heat sensitive, destroyed by pronase, and neutralized by anti-human whole serum. The CF serum retained agglutinating activity following preincubation with anti-human IgG, IgA, B(1)E, and B(1)A/B(1)C.